Gender Equality and Sustainable Development in Nigeria - Toriola Anu Keshiro, Oyewole Adegboyega Sule, Ayanwole Ayanyemi Adeyemi, Adebosin Walid Gbadebo; Yemi, & Balogun Kamildeen (Covenant Journal of Entrepreneurship, 2018)
Sustainable development is development that meets the basic needs of the present generation in a way that did not affect the ability of the future generation to meet their needs. Gender equity serves as an essential building block for this kind of development. Despite the changes in the approach used in addressing social, economic and environmental issues in Nigeria, the achievement of developmental goals still remain a mirage. Women by the social settings carry out more responsibility that are not paid which constraint their capacity to fight for their rights. This study therefore examines gender equality and sustainable development in Nigeria. The study specifically examines the magnitude of the relationship between gender equality and sustainable development and investigates how the relationship between men and women affect sustainable development in Nigeria. Annual time series data sourced from the World Bank Development Index (WDI) covering the period of 2001 to 2016 was used in the study. As preliminary tests, descriptive and graphical trend analysis, and unit root test was conducted while the correlation analysis, OLS regression analysis and Granger causality test were employed in the actual estimation. The correlation analysis indicates a positive very strong correlation between gender equality index and sustainable development index (r=Â 0.734) while a positive weak correlation was evident in the association between environmental performance proxy by emission of CO2 and sustainable development index (r=Â 0.733). The OLS regression estimate showed a significant positive relationship between the sustainable development and Gender equality (=7.652, t=2.780, p<0.05) and a negative significant relationship between environmental performance and sustainable development (=-3.654, t=6.868, p<0.05). The main submission from the result is that, gender equality has a significant positive relationship with sustainable development in Nigeria. The study recommends the need to encourage equitable and responsible participation of men and women at the different level where decisions are made and control is exercised by government and policy makers.